2009
DOI: 10.1002/elan.200804509
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Characterization of Epigallocatechin Gallate Using Square‐Wave Voltammetry

Abstract: Electrochemical oxidation of (À)-epigallocatechin gallate (EGCG), the main monomer flavanol found in green tea, has been investigated over a wide pH range at a glassy-carbon electrode using square-wave voltammetry (SWV). Square-wave voltammograms of (À)-epigallocatechin (EGC) and gallic acid have been studied as well. The I -E profile of EGCG, i.e. the oxidation potentials and the current responses of the first and the second peak, is pH dependent. The oxidation of EGCG is a quasireversible process over the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
50
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 31 publications
8
50
0
Order By: Relevance
“…The accuracy of the results has been compared by HPLC technique. In these works of Komorsky-Lovric et al [125,126] it has been shown that SWV sensitivity and selectivity is comparable to that obtained by chromatographic techniques. In another work, SWV has been explored for quantification of polyphenols from the class of flavonolignans [127].…”
Section: Analytical and Biochemical Applications Of Square-wave Voltamentioning
confidence: 84%
See 1 more Smart Citation
“…The accuracy of the results has been compared by HPLC technique. In these works of Komorsky-Lovric et al [125,126] it has been shown that SWV sensitivity and selectivity is comparable to that obtained by chromatographic techniques. In another work, SWV has been explored for quantification of polyphenols from the class of flavonolignans [127].…”
Section: Analytical and Biochemical Applications Of Square-wave Voltamentioning
confidence: 84%
“…The linear dependence between the net SW peak currents and the phenolic substrates concentration was found even in the sub-nanomolar concentration range of studied phenols. Polyphenols from the group of flavonols present in various plants have been also determined by using SWV with solid electrodes [125,126]. Various catechins such as epigallocatechin gallate, epicatechin, epicatechin gallate, gallic acid and epigallocatechin were directly quantified in various green teas in submicromolar concentration ranges by using SWV with a glassy carbon as a working electrode.…”
Section: Analytical and Biochemical Applications Of Square-wave Voltamentioning
confidence: 99%
“…Despite the fact that gallic acid is the polyphenolic acid commonly used as reference for the TPC expression, in the present work RA was selected due to the fact that in the experimental conditions optimized in this study, RA presents a simpler voltammetric behavior, with only one quasireversible well-defined oxidation peak, in comparison with gallic acid and catechins which exhibit two irreversible oxidation peaks. On the other hand, the RA oxidation peak is situated in the same potential range with the oxidation peak of gallic acid and catechins (Novak et al 2009). …”
Section: Introductionmentioning
confidence: 81%
“…DPV recordings on PGE in 0.1 M H 2 SO 4 have shown that other polyphenolic acids (e.g. caffeic acid, chlorogenic acid, gallic acid) (Novak et al 2009;David et al 2015a) are oxidized at almost the same potential. Therefore the developed method can't be applied for the determination of RA in tea samples, but it was observed that the current intensity of this peak increased linearly with three successive additions of 0.1 mL stock solution of 10 −4 M RA (Fig.…”
Section: Recovery Studies and Analytical Applicationsmentioning
confidence: 99%
“…It is widely recognised that the curbing of many diseases (Aruoma, 1998;Belitz & Grosch, 1999;Bogeski, Kappl, Kummerow, Gulaboski & Hoth, 2011;Cadenas & Davies, 2000;Droge, 2002;Halliwell & Gutteridge, 2002;Stanner, Hughes, Kelly, & Buttriss, 2004) is directly linked to consumption of bioactive compounds such as vitamins A, D, K and E, lipoic acid, and many polyphenolic derivatives as hydroquinones and flavonoids (Beardsell, Francis, & Ridley, 2002;Manach, Scalbert, Morand, & Jimenez, 2004;Novak, Seruga, & Komorsky-Lovric, 2009, 2010Visioli, Bogani, Grande, & Galli, 2004;Yanishlieva-Maslarova & Heinonen, 2001;Yu, Zhou, & Parry, 2005). Cold-pressed edible vegetable oils are rich in a variety of lipophilic vitamins and polyphenols (Beardsell et al, 2002;Belitz & Grosch, 1999;Manach et al, 2004;Visioli et al, 2004;Yanishlieva-Maslarova & Heinonen, 2001;Yu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%